Brand Equity and Business Performance: Towards a Conceptual Framework - Mohan, Bijuna C.; Sequeira, A. H. (Indian Journal of Marketing, 2013)
A Brand is considered to be one of the most important intangible assets of any business. Companies spend a considerable amount of their revenue and time on brand building activities. In this scenario, there arose a need for the justification of brand building activities. Brand equity and business performance are the two concurrent topics of interest to both managers and academicians. This study examines the relationship between brand equity and business performance in the Fast Moving Consumer Goods (FMCG) industry. By understanding the dimensions of brand equity, the study focuses on the important contributors to brand equity. This article focuses on the studies establishing the relationship between brand equity and business performance, in which brand equity dimensions, i.e. - brand awareness, brand loyalty, perceived quality and brand associations - are related to business performance. Building on existing conceptual and empirical data, a conceptual framework of such a relationship was developed. The proposed framework can serve as a reference framework to leverage the business performance in the brand management process.